Classic Media Reviews. (1st June 2016) - Hart, Kylo-Patrick R.; Pugh, Tison
THE MYSTERIES OF PITTSBURGH, DIRECTED BY RAWSON MARSHALL THURBER (2008) Los Angeles: Groundswell ProductionsBEAT THE DEVIL, DIRECTED BY JOHN HUSTON, SCREENPLAY BY TRUMAN CAPOTE, STARRING HUMPHREY BOGART (1953) Los Angeles: Santana Pictures